Hulaguid, Chagatai and Timurid Armor Garments with In ternally Sewn and Riveted Plates, Fourteenth–Fifteenth Centuries: On Some Features of Design and Cut - Leonid A. Bobrov; Aibolat K. Kushkumbayev (Oriental Studies)
Introduction. The paper considers body armor patterns with hidden plates worn by warriors of Hulaguid Iran, Chagatai Ulus, and the Timurid Empire. In contemporary weapon studies, such armor is known as ‘kuyak’ or ‘brigandine’. Goals. The study aims at identifying features of design and cut inherent to some types of Hulaguid, Chagatai and Timurid ‘kuyaks’ from the fourteenth–fifteenth centuries. Results. Comparative insights into archaeological and graphic materials yield a hypothesis there may have existed a special variety of combined ‘kuyaks’ with some plates riveted and some sewn to an organic backing on the inside. Such armor garments could have been used by warriors of Hulaguid Iran in the late thirteenth or early fourteenth centuries. From a historical perspective, such armors could be a variation between thirteenth-century armor garments with sewn-in plates and — ‘brigandines’ with riveted-in plates of the subsequent era. Our comprehensive analysis of written and graphic data also concludes that the late fourteenth and fifteenth centuries in Transoxiana, Khorasan and adjacent territories were characterized by a widespread occurrence of special plated-and-riveted armors combining an armored torso part and a long unarmored skirt. The unusual design resulted from the appearance and spread of a new mail-and-plate hip defense element referred to as ‘dyzlyq-butluq’, which made the heavy armored Central Asian skirts not that relevant. In view of the armors’ distribution area, they can be labeled as ‘Timurid-type kuyaks’. Conclusions. The replacement of ‘Timurid-type’ armors (with riveted-in plates) from combat practices of Central Asian peoples was caused by a change in the local military-cultural tradition in the aftermath of collapses of the Timurid states throughout the early sixteenth century.